Use of negative stiffness in failure analysis of concrete beams. (1st November 2016) - Al-Sabah, A. Salam; Laefer, Debra F.
Highlights: New method for damage analysis of concrete using negative stiffness. Efficient, incremental-only solution. Instability resulting from negative stiffness was controlled by incrementing damage. More efficient than sequentially linear analysis and simpler than full non-linear finite element. New method was used to solve two examples with reasonable accuracy. Abstract: A new concrete analysis method is presented entitled continuous, incremental-only, tangential analysis (CITA). CITA employs piece-wise linear stress-strain curve and a tangent elasticity modulus to calculate stiffness including parts with negative values. Since indefinite structure stiffness matrices generally indicate instability, traditionally they have been avoided. However, since CITA analysis involves introducing damage in steps, the full range of concrete behaviour including the softening portion under tensile cracking can be addressed. Herein CITA is verified against numerical and experimental results for concrete beams, thereby showing faster solutions for non-linear problems than sequentially-linear analysis, while reducing self-imposed restrictions against negative stiffness.